2019
DOI: 10.1186/s13048-019-0548-7
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of HSP70 may contribute to PCOS pathology

Abstract: Background The mechanism of the pathological change of polycystic ovary syndrome (PCOS) is still unclear. Previous studies have shown that PCOS is a chronic nonspecific low-grade inflammatory condition, and that heat shock protein (HSP)70 has a potent anti-inflammatory property. So the aim of this study is to investigate the correlation between HSP70 and the hormones and inflammatory factors and to find out the role of HSP70 in the pathogenesis of PCOS. Methods Twenty f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…In our study, Spearman rank correlation analysis showed that serum HSP70 levels were signi cantly negatively correlated with IL-10 and TGF-β levels, while signi cantly positively correlated with IL-6, IL-17, IL-23 and other in ammatory cytokines. Our previous study has shown that the levels of serum heat shock protein 70 in PCOS rats were decreased, and they were strongly negative correlated to testosterone, luteinizing hormone and in ammatory factors such as C-reactive protein, IL-6, IL-18, and tumor necrosis factor-α [27] This is contrary to our results in PCOS patients. The possible reason is that the transient superphysiological testosterone characteristics caused by the construction of PCOS rat model downregulated the expression of HSP70 in rat serum.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, Spearman rank correlation analysis showed that serum HSP70 levels were signi cantly negatively correlated with IL-10 and TGF-β levels, while signi cantly positively correlated with IL-6, IL-17, IL-23 and other in ammatory cytokines. Our previous study has shown that the levels of serum heat shock protein 70 in PCOS rats were decreased, and they were strongly negative correlated to testosterone, luteinizing hormone and in ammatory factors such as C-reactive protein, IL-6, IL-18, and tumor necrosis factor-α [27] This is contrary to our results in PCOS patients. The possible reason is that the transient superphysiological testosterone characteristics caused by the construction of PCOS rat model downregulated the expression of HSP70 in rat serum.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the hormones and ovarian morphology changes in the DHEA-induced PCOS and PCOS + glutamine rats were in accordance with the characteristic of PCOS patients as previous studies [2,9]. Significant decrease in the level of some amino acids including glutamine was observed in plasma in PCOS patients compared with the controls, these changes reflect the various metabolic pathways that participate in physiological functions [10].…”
Section: Discussionsupporting
confidence: 90%
“…The rats were randomly assigned into five groups (n = 10 /group), control group, PCOS group, PCOS + 0.5 g/kg Gln group, PCOS + 0.75 g/kg Gln group and PCOS + 1.0 g/kg Gln group. The PCOS rat model was established according to our previous study [9]. Briefly, all the PCOS rats were daily injected (subcutaneously) with 6 mg/100 g dehydroepiandrosterone (DHEA) (Aladdin Reagent Co., Ltd., Shanghai, China) which was dissolved in olive oil for 20 consecutive days, the control group was injected with an equivalent olive oil for 20 consecutive days.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…High levels of phosphorylated NF-κB in uterine tissues suggested an increase in uterine inflammation. Chronic low-grade inflammation plays an important role in the pathogenesis of PCOS [ 45 ]. Patients with PCOS clearly have increased serum C-reactive protein (CRP) and pro-inflammatory cytokine levels, including TNF-α, IL-1β, and IL-6 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%